Bridging theory and practice in healthy aging: the role of wellness tourism in shaping psychosocial outcomes - Azadeh Azimi; Erfan Moradi; Bahram Yousefi; Zohreh Hassani (Acta Psychologica)
The global aging phenomenon necessitates innovative interventions to enhance the health and psychosocial well-being of older adults. This study investigates the potential of wellness tourism, specifically through wellness resorts, as a strategy for promoting healthy aging in Iran. Grounded in attention restoration theory (ART) and socioemotional selectivity theory (SST), the research examines how key psychosocial factors—namely, life satisfaction and the perceived restorative quality of the environment—mediate the relationship between wellness tourism experiences and overall well-being. Data were collected via structured surveys administered to senior tourists at Iranian wellness resorts. Partial Least Squares Structural Equation Modeling was employed to assess both direct and indirect relationships among the constructs, while fuzzy-set Qualitative Comparative Analysis was used to identify optimal pathways that lead to enhanced well-being. The findings reveal that wellness tourism experiences significantly influence life satisfaction and perceived restorative environments, which in turn contribute to improved well-being among older adults. A gender-based multi-group analysis further demonstrates nuanced differences: older women benefit more from the mediating effect of life satisfaction, whereas perceived restorative environments exert a stronger direct influence on the well-being of older men. These results not only validate the applicability of ART and SST in a novel context but also extend these theoretical frameworks by highlighting the importance of gender-specific and culturally contingent mechanisms in wellness tourism. The study's insights offer important implications for public health and aging policies. It is recommended that policymakers develop gender-sensitive wellness tourism programs and implement supportive measures—such as financial subsidies, targeted awareness campaigns, and improved accessibility—to optimize health outcomes for older populations, particularly in developing nations. Overall, this research underscores the multifaceted benefits of wellness tourism as an integrative component of healthy aging strategies.